2008
DOI: 10.2353/ajpath.2008.080060
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Promotes Lymphangiogenesis

Abstract: The lymphatic system plays an important role in inflammation and cancer progression, although the molecular mechanisms involved are poorly understood. As determined using comparative transcriptional profiling studies of cultured lymphatic endothelial cells versus blood vascular endothelial cells, growth hormone receptor was expressed at much higher levels in lymphatic endothelial cells than in blood vascular endothelial cells. These findings were confirmed by quantitative real-time reverse transcriptase-polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 71 publications
(99 reference statements)
3
27
0
Order By: Relevance
“…Finally, the arterial marker ephrinB2 was up-regulated only by NICD, but not by Hey1, Hey2, or Hes1. We also found that activated NICD strongly down-regulated a number of other previously reported lymphatic markers, including coxsackie virus and adenovirus receptor, 42,43 c-Maf, 14,44 plakoglobin, 13 transforming growth factor-␣, 14 aldehyde dehydrogenase 1 A1, 14 and growth hormone receptor 14,45 (Table 2). Taken together, these data indicate that Notch signal suppresses the lymphatic phenotypes and possibly augments the arterial phenotype in postdevelopmental LECs.…”
Section: Notch Signal Regulates Other Lymphatic Markerssupporting
confidence: 64%
“…Finally, the arterial marker ephrinB2 was up-regulated only by NICD, but not by Hey1, Hey2, or Hes1. We also found that activated NICD strongly down-regulated a number of other previously reported lymphatic markers, including coxsackie virus and adenovirus receptor, 42,43 c-Maf, 14,44 plakoglobin, 13 transforming growth factor-␣, 14 aldehyde dehydrogenase 1 A1, 14 and growth hormone receptor 14,45 (Table 2). Taken together, these data indicate that Notch signal suppresses the lymphatic phenotypes and possibly augments the arterial phenotype in postdevelopmental LECs.…”
Section: Notch Signal Regulates Other Lymphatic Markerssupporting
confidence: 64%
“…Newly identified lymphangiogenic factors include the growth hormone (GH), 88 and the multifunctional peptide adrenomedullin (AM), which signals via the calcitonin receptor-like receptor (calcrl) associated with the receptor activity modifying protein (RAMP) 2. In addition to AM signaling having a role in lymphatic development as revealed by knockout mice for either AM itself or calcrl or RAMP2 (Table 1), adrenomedullin treatment promotes the proliferation of cultured human LECs.…”
Section: Lymphangiogenesis In the Adultmentioning
confidence: 99%
“…Growth hormone is produced steadily during childhood, doubles in production during puberty [13], and is known to promote lymphangiogenesis [14]. Recently, a study of LM tissue found an overexpression of GH receptors (65%) compared to the control tissue (25.8%), which suggests that GH may play a role in LM pathophysiology and influencing disease progression [15].…”
Section: Discussionmentioning
confidence: 99%